The psychology of bulimia nervosa : a cognitive perspective - Cooper, Myra, 1957- (Oxford University Press, 2003)
This text provides a detailed review of the key psychological aspects of bulimia nervosa and places some emphasis on cognitive considerations. The coverage includes key features, associated problems, psychological theories and different treatment approaches.